Diabetes distress prevalence, determinants and its association with the treatment regimen -A cross sectional study from north-east India - Veeraraghavan, V; Agrawal, D; Singh, A (Journal of Diabetes and Endocrinology Association of Nepal, 2023)
Background: Diabetes distress (DD) in India has always been studied along with depression. There are no studies explaining the prevalence, correlation with diabetes management. This is study is first of its kind from northeast India. Methods: The aim of this study was to estimate the prevalence of DD and determine the socio-demographic variables. Focus was also on the relationship between treatment regimen and diabetes distress. A cross sectional study was conducted in a tertiary care hospital in Guwahati, Assam. DD scale was administered on 226 patients reporting to the medicine outpatient department. Data on treatment regimen for diabetes mellitus was collected and formulated. Sample size calculation was done according to the prevailing prevalence estimates. Statistical tests like ANOVA, independent t-tests and regression analysis were used. Results: DD was found to have a prevalence of 43% in our study. Duration of diabetes, sedentary lifestyle, and low education were associated with higher distress levels. Patients on insulin were found to have greater distress when compared with patients on oral hypoglycaemic agents. Conclusion: DD was found to have higher prevalence in our study. This influences the self-care in diabetes. DD specific modalities have to be incorporated in conventional treatment of diabetes mellitus. Early screening should be foci of interest.